NUTRITIONAL ASPECTS OF PREGNANT AND LACTATING WOMEN - Akhmedova Rokhila Umarkhojayevna (Scholar Express Journals, 2023)
Pregnancy and lactation are critical periods in a woman's life that demand special attention to nutritional needs. This article explores the importance of proper nutrition during these phases, reviews relevant literature, discusses methods for achieving optimal nutrition, presents key findings, and offers conclusions and suggestions for promoting the well-being of pregnant and lactating women.
Keywords: Pregnancy; lactation; nutrition; micronutrients